The Effect of Profitability, Leverage, and Company Size on Tax Aggressiveness - Fachruddin, Muhammad; Mulia, Teodora Winda (Universitas KH. Abdul Chalim Mojokerto, 2026)
The aim of this study was to examine the impact of earnings capability, capital structure, and company scale on tax aggressiveness within healthcare sub-sector firms registered on the Indonesia Stock Exchange (IDX) throughout the 2018–2024 timeframe. This investigation applied a numerical research design utilizing secondary information sourced from the corporations’ yearly financial statements. The sampling method adopted was purposive selection, producing 84 firm-year data points that satisfied the established requirements. Data evaluation employed panel regression analysis accompanied by a set of classical assumption examinations, including distribution normality, variable collinearity, variance inconsistency, and serial correlation checks, to guarantee the dependability and accuracy of the model. The findings indicated that earnings capability, capital structure, and company scale collectively exerted a positive and significant influence on tax aggressiveness, indicating that firms with higher profitability, greater leverage, and larger size tend to engage more in tax management strategies to minimize tax obligations. However, when tested partially, each variable demonstrated only a modest individual effect, suggesting that tax aggression behavior is influenced by a combination of financial and structural characteristics rather than a single factor. The outcomes of this research deliver perspectives for regulators and business executives to more comprehensively grasp the factors shaping fiscal conduct and to encourage more transparent and responsible tax compliance practices in the healthcare industry.